Difficulties in implanting a team of technicians in an eye bank at an university hospital - Gabriel, Débora Cristina; Sato, Elcio Hideo (Brazilian Journal of Transplantation, 2008)
Purpose: To determine main difficulties and impacts experienced by technicians from the São Paulo Hospital’s Eye Bank in the beginning of their work, and to identify their needs concerning preparation and training, aiming to improve the quality. Methods: It was applied a questionnaire on the difficulties and impacts experienced by technicians from the Hospital São Paulo’s Eye Bank, University Hospital to four professionals of that team. Results: Qualitative analysis of answers showed that difficulties were: lack of experience in the recovering the donated tissue technique; unsafe night conditions along the way to the morgue, the hospital’s transportation scarcity to collect external donations. According to the questionnaire, the major impact was interviewing possible donors’ families. Conclusion: It is necessary to prepare and perform specific training to technicians of the Eye Bank for a duty that requires practice and ability, which will be acquired upon applying the right technique in several donations. Great importance should be given to such specific preparation to perform the family interview in order to avoid the eye donation becomes a negative experience.